Landscapes Defined - King-Hildreth, Julie (My University, 2013)
Landscape paintings are records of time and place and change. A landscape painting is looking at the land through someone else?s eyes. Choosing this subject matter, a person may find out that it is a process of discovering the many layers involved in the art of painting nature. From researching artists, I wonder: What inspires artists to want to paint the land and what techniques and styles do those artists use in their paintings? What elements and principles of art are focused on? As they painted what and how they created their work evolved into their own style. From researching these artists and painting landscapes myself, I discovered that there are specific elements in the landscapes I am attracted to and use in my own work. As a teacher I would like to explore the basic characteristics of landscape paintings from artists that have made an impact on my own learning and in turn teach that to my students.
Plan B Paper. 2013. Master's of Science Education. Art Department. 33 leaves. Includes bibliographical references (leaves 32-33).
Keywords: Landscape painting--Study and teaching; Landscape painting--Technique